2013
DOI: 10.4103/2141-9248.117933
|View full text |Cite
|
Sign up to set email alerts
|

Yoga for high-risk pregnancy: A randomized controlled trial

Abstract: Background:Improvements in technology have increased the chances of survival for the micro-premature infant and the very low birth-weight infant but have significantly increased the financial burden of health care organizations. This economic burden has a significant impact on third-party payers and on society in general.Aim:The study was designed to assess yoga therapy (YT) module on maternal stress level in high risk pregnancy.Subjects and Methods:In the present study, sixty-eight pregnant women (38 in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 18 publications
(20 reference statements)
0
13
0
2
Order By: Relevance
“…Twenty‐eight RCTs reported results of 1944 pregnant women. Nine RCTs were conducted in West Asia (Iran (Asghari et al., 2016; Bastani et al., 2005; Khorsandi et al., 2016; Mohammad & Shima, 2019; Nasiri et al., 2018; Shahtaheri et al., 2016; Zaheri et al., 2017) and Turkey (Ertekin et al., 2018; Fiskin & Sahin, 2018)); seven in Europe (Greece (Kantziari et al., 2019; Tragea et al., 2014), Germany (Richter et al., 2012), Ireland (Matvienko‐Sikar & Dockray, 2017), Sweden (Lönnberg et al., 2020; Scherer et al., 2016) and UK (Krusche et al., 2018)); five in USA (Guardino et al., 2014; Jallo et al., 2014; Urizar et al., 2019; Vieten & Astin, 2008; Zhang & Emory, 2015); three in India (Deshpande et al., 2013; Muthukrishnan et al., 2016; Satyapriya et al., 2009); two in China (Pan et al., 2018; Zhang et al., 2019); and two in Australia (Beattie et al., 2017; Woolhouse et al., 2014). The mean age of the participants ranged from 18 to 35 years old.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐eight RCTs reported results of 1944 pregnant women. Nine RCTs were conducted in West Asia (Iran (Asghari et al., 2016; Bastani et al., 2005; Khorsandi et al., 2016; Mohammad & Shima, 2019; Nasiri et al., 2018; Shahtaheri et al., 2016; Zaheri et al., 2017) and Turkey (Ertekin et al., 2018; Fiskin & Sahin, 2018)); seven in Europe (Greece (Kantziari et al., 2019; Tragea et al., 2014), Germany (Richter et al., 2012), Ireland (Matvienko‐Sikar & Dockray, 2017), Sweden (Lönnberg et al., 2020; Scherer et al., 2016) and UK (Krusche et al., 2018)); five in USA (Guardino et al., 2014; Jallo et al., 2014; Urizar et al., 2019; Vieten & Astin, 2008; Zhang & Emory, 2015); three in India (Deshpande et al., 2013; Muthukrishnan et al., 2016; Satyapriya et al., 2009); two in China (Pan et al., 2018; Zhang et al., 2019); and two in Australia (Beattie et al., 2017; Woolhouse et al., 2014). The mean age of the participants ranged from 18 to 35 years old.…”
Section: Resultsmentioning
confidence: 99%
“…The study of Ganpat et al (2013) showed that the prenatal yoga module can reduce stress levels during high-risk pregnancy complications. So, practicing prenatal yoga during a high-risk pregnancy is not only a cost-effective option but also a viable and safe option.…”
Section: The Effect Of Prenatal Yoga Onmentioning
confidence: 99%
“…Deshpande ve ark. 'nın (4) aromaterapi: Aromaterapi, "tamamen bitkilerden elde edilen yağların kullanımı", "terapötik uçucu yağların inhalasyon yoluyla koklanarak ya da diğer yollarla iyileştirmesi" ve "bitkilerden elde edilen uçucu yağların masaj, friksiyon, inhalasyon, kompres ve banyo yoluyla uygulanarak doğal tedavi sağlaması" sözleri ile tanımlanmaktadır (24) . Hipertansiyonda kan basıncını kontrol altına almak için aromaterapide kullanılan birçok yağ mevcuttur.…”
Section: Preeklampsi Bakımında Tamamlayıcı Tıpunclassified
“…Hastalığın tedavisinde ve önlenmesinde erken teşhis ve hastalığın doğru yönetimi çok önemlidir. Preeklampsinin tanılanma, değerlendirilme ve yönetiminde hemşireler kritik bir role sahiptir (3,4) . Paauw ve ark.…”
Section: Introductionunclassified